The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0310057x1504300109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of a Low Central Venous Oxygen Saturation after Major Surgery: A Prospective Prevalence Study

Abstract: Optimising perioperative haemodynamic status may reduce postoperative complications. In this prospective prevalence study, we investigated the associations between standard haemodynamic parameters and a low central venous oxygen saturation (ScvO 2 ) in patients after major surgery. A total of 201 patients requiring continuous arterial and central venous pressure monitoring after major surgery were recruited. Simultaneous arterial and central venous blood gases, haemodynamic and biochemical data and perfusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…acute pulmonary embolism), use of fluid boluses to increase CVP to a high level may be harmful, as the right heart is very prone to dilate with excessive filling and the left heart can be paradoxically under-filled due to interventricular dependency 12 . Other studies have also shown that CVP has no discriminative value in predicting adequacy of systemic oxygen delivery for patients after major surgery 13 and is not reliable in predicting the size or collapsibility of the superior vena cava 14 . Despite the use of ultrasound technology, serious mechanical complications related to central venous catheterisation can still occur 15 .…”
Section: Central Venous Pressurementioning
confidence: 98%
See 1 more Smart Citation
“…acute pulmonary embolism), use of fluid boluses to increase CVP to a high level may be harmful, as the right heart is very prone to dilate with excessive filling and the left heart can be paradoxically under-filled due to interventricular dependency 12 . Other studies have also shown that CVP has no discriminative value in predicting adequacy of systemic oxygen delivery for patients after major surgery 13 and is not reliable in predicting the size or collapsibility of the superior vena cava 14 . Despite the use of ultrasound technology, serious mechanical complications related to central venous catheterisation can still occur 15 .…”
Section: Central Venous Pressurementioning
confidence: 98%
“…This result was subsequently confirmed by similar studies and mathematical modelling [28][29][30] . Even in patients without obvious extreme hyperoxaemia, PaO 2 remains the most important factor in determining CvO 2 in patients after major surgery 13 . In fact, hyperoxaemia (mean PaO 2 >120 mmHg) was common in patients recruited in the RCT on EGDT 22 , making the algorithm aiming at a high CvO 2 without considering the effect of hyperoxaemia on CvO 2 vulnerable to uncontrolled bias.…”
mentioning
confidence: 99%
“…Central venous pressure has previously been used to guide peri‐operative fluid therapy, but a CVP of between 5 mmHg to 20 mmHg has certainly almost no predictive value, and changes in CVP with a fluid bolus have not been shown to be predictive of fluid status . Central venous pressure is well‐known to be affected by other variables, such as intrathoracic pressure, venous resistance and pulmonary vascular resistance, and a recent study demonstrated that there is little value in using CVP as a marker of adequate systemic oxygen delivery after major surgery .…”
Section: Haemodynamic Monitoring and Variablesmentioning
confidence: 99%
“…Arterial oxygen content = (1.34 × arterial oxygen saturation Inadequate systemic oxygen delivery or occult tissue hypoperfusion was defined by an O 2 ER >0.3 in this study, because a S CV O 2 <70% is widely considered as signifying inadequate systemic oxygen delivery resulting in increased tissue oxygen extraction 1,2,6 . CO 2 gap: central venous CO 2 tension -arterial CO 2 tension.…”
Section: Haemodynamic Calculationsmentioning
confidence: 99%